Aplikasi Pembayaran Iuran SMK Negeri 1 Lenangguar Menggunnakan Framework Codeigniter - Pranata, Dody; Dery Sofya, Nora (Management of Information System Journal, 2023)
In various fields of human life today, technology continues to experience very rapid development, such as the use of technology in paying school fees. Payment of school fees aims to support the quality of learning. SMK Negeri 1 Lenangguar is currently processing school tuition payments by writing them on a ledger. This manual recording process has drawbacks such as frequent damage to data storage media, errors in data recording and loss of data which hinders financial reporting. Seeing this, the researchers designed a school tuition payment application using the codeigniter framework and extreme programming as a software development method. Researchers also use Unified Modeling Language (UML) as a system design method.